2009
DOI: 10.1002/uog.6359
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal sonographic diagnosis of skeletal dysplasias

Abstract: Objective To assess the types and numbers of cases, gestational age at specific prenatal diagnosis and diagnostic accuracy of the diagnosis of skeletal dysplasias in a prenatal population from a single tertiary center. (88% and 89%, respectively) at the first diagnostic examination. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
144
1
17

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(170 citation statements)
references
References 18 publications
8
144
1
17
Order By: Relevance
“…A prenatal diagnosis is therefore feasible technically by the time of the anomaly scan but it can be challenging owing to either intrinsic limitations or technical problems, such as fetal lie, decreased amount of amniotic fluid or maternal obesity 5 . Early prenatal diagnosis enabled us to offer the parents detailed multidisciplinary counseling and to anticipate the different clinical scenarios that could occur at birth and the specific treatment options available.…”
Section: Prenatal Diagnosis Of Gollop-wolfgang Complexmentioning
confidence: 99%
“…A prenatal diagnosis is therefore feasible technically by the time of the anomaly scan but it can be challenging owing to either intrinsic limitations or technical problems, such as fetal lie, decreased amount of amniotic fluid or maternal obesity 5 . Early prenatal diagnosis enabled us to offer the parents detailed multidisciplinary counseling and to anticipate the different clinical scenarios that could occur at birth and the specific treatment options available.…”
Section: Prenatal Diagnosis Of Gollop-wolfgang Complexmentioning
confidence: 99%
“…Literatūros duomenimis, 89 proc. OI atvejų, įtartų atlikus ultragarsinį tyrimą, buvo patvirtinti [11]. Šis tyrimo metodas ypač reikšmingas diagnozuojant II ir III tipo OI, nes lengvesnių OI formų atvejais būdin-gi požymiai išryškėja nėštumo pabaigoje ar naujagimystės laikotarpiu.…”
Section: Diskusijaunclassified
“…Šis tyrimo metodas ypač reikšmingas diagnozuojant II ir III tipo OI, nes lengvesnių OI formų atvejais būdin-gi požymiai išryškėja nėštumo pabaigoje ar naujagimystės laikotarpiu. Atliekant ankstyvąją ultragarsinę patikrą 12-14 sav., būdinga sustorėjusi sprando srities vaiskuma, neryškūs ilgųjų kaulų akustiniai šešėliai bei ilgųjų kaulų sutrumpė-jimas ar išlinkimas [9,11]. Vėliau atsiranda kitų požymių, priklausančių nuo ligos tipo: labai gerai vizualizuojamos galvos struktūros, kaukolės skliauto deformacija nuo spaudimo davikliu, plokščias veido profilis, plokščia krūtinės ląs-ta sagitaliniame pjūvyje, banguoti šonkauliai, varijuojantis sulinkusių ar lūžusių ilgųjų kaulų skaičius, apatinės galūnės pažeistos stipriau nei viršutinės, equinovarus, kartais polihidramnionas ir kt.…”
Section: Diskusijaunclassified
See 1 more Smart Citation
“…The vast number of different skeletal dysplasias means that achieving a precise diagnosis in utero is difficult in the absence of family history. However Schramm et al 37 reported a large series of 178 patients diagnosed with suspected skeletal dysplasia in utero 37 and showed that a skeletal dysplasia was confirmed in 160 of these cases and that lethality was accurately predicted using the fetal thoracic to abdominal ratio, a lower ratio indicating pulmonary hypoplasia 35 . Identification of extra-skeletal anomalies such as polydactyly also aided diagnosis.…”
Section: Suspected Skeletal Dysplasiamentioning
confidence: 99%